Learning for the transfer of knowledge in research centers of the Colombian coffee industry - Marulanda, Carlos Eduardo (Scientia et Technica, 2019)
The findings presented in this article are based on the results of a research on the incidence of learning in the transfer of knowledge in 24 research centers and institutes of the Colombian coffee triangle. Based on a qualitative research and with types of descriptive and correlational study. It can be concluded that organizational learning is a key factor for the transfer of knowledge and it is intended that the presented results formulate strategies in these organisms to advance knowledge transfer